2023
DOI: 10.3390/pharmaceutics15020343
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Quercus dalechampii Ten. and Q. frainetto Ten. Barks Extracts as Antimicrobial, Enzyme Inhibitory, Antioxidant and Cytotoxic Agents

Abstract: The bark resulted as a by-product after different Quercus sp. processing is a valuable alternative source of phenolic compounds (mainly tannins). Hence, the focus of the present work was to obtain eight extracts from the rhytidome of the less-studied Q. dalechampii and Q. frainetto and characterize them in terms of chemical and bioactive profiles. Ultrasound and microwave-assisted extraction methods were used for the preparation of the extracts. Total phenolic and tannin contents were assessed through classic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Inhibiting tyrosinase is of interest in the treatment of skin hyperpigmentation caused by overproduction of melanin, with relevance in both pharmaceutical and cosmetic fields. Numerous studies have demonstrated the effectiveness of extracts obtained from the barks of various trees as anti-tyrosinase agents (Tanase et al 2019b(Tanase et al , 2023. The analyzed extract was found to exert weak inhibitory action on this enzyme, given that the literature cites IC50 values of 4.44 μg/mL for the positive control used in this test (kojic acid).…”
Section: In Vitro Enzyme Inhibitory Properties Of Opth Extractmentioning
confidence: 98%
See 2 more Smart Citations
“…Inhibiting tyrosinase is of interest in the treatment of skin hyperpigmentation caused by overproduction of melanin, with relevance in both pharmaceutical and cosmetic fields. Numerous studies have demonstrated the effectiveness of extracts obtained from the barks of various trees as anti-tyrosinase agents (Tanase et al 2019b(Tanase et al , 2023. The analyzed extract was found to exert weak inhibitory action on this enzyme, given that the literature cites IC50 values of 4.44 μg/mL for the positive control used in this test (kojic acid).…”
Section: In Vitro Enzyme Inhibitory Properties Of Opth Extractmentioning
confidence: 98%
“…The inhibitory potential of OpTh on the tyrosinase enzyme, which is involved in various metabolic processes and biochemical reactions, was examined using in vitro tests adapted for a microplate reader (Tanase et al 2023). The metabolic processes in which tyrosinase is involved include protein synthesis, hormone synthesis, neurotransmitter synthesis, pigment synthesis, and melatonin production.…”
Section: Determination Of Tyrosine Inhibitory Activitymentioning
confidence: 99%
See 1 more Smart Citation